Stoves for every taste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The variety of improved cookstoves on the market increases each year. Different materials, uses and energy sources now enable people to choose the model most appropriate for their needs. Large-scale stoves designed for communal use have now...